2022
DOI: 10.3389/fnagi.2022.985109
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dementia or cognitive impairment in non-alcoholic fatty liver disease: A systematic review and meta-analysis

Abstract: ObjectivesTo investigate whether non-alcoholic fatty liver disease (NAFLD) increases the risk of dementia or cognitive impairment.MethodsA systematic search of the literature in the PubMed, Excerpta Medica Database (EMBASE), Cochrane Library, and Web of Science databases was conducted, covering the period from the inception of each database to 22 May 2022. Statistical analysis of non-alcoholic fatty liver disease and the risk of cognitive impairment or dementia based on data extracted from each article was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
(96 reference statements)
1
9
1
Order By: Relevance
“…A high percentage of liver fat led to a reduced risk of Alzheimer's disease and dementia. Past studies 120,121 have reported associations between the two and our results aligned with the most recent study 122 . Further research is necessary to elucidate the underlying pathophysiological mechanism.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 92%
“…A high percentage of liver fat led to a reduced risk of Alzheimer's disease and dementia. Past studies 120,121 have reported associations between the two and our results aligned with the most recent study 122 . Further research is necessary to elucidate the underlying pathophysiological mechanism.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 92%
“…While some traditional risk factors, such as AUD and viral hepatitis, were associated with high FIB-4 scores, others (eg, diabetes and hyperlipidemia) were not. Although the reasons are unclear, diabetes and hyperlipidemia are associated with vascular dementia, independent of liver disease . Depression and PTSD, which are known to be occur more often among people with cirrhosis than the general population, were not associated with high FIB-4 scores in this analysis.…”
Section: Discussionmentioning
confidence: 57%
“…The quality of human studies was evaluated by Agency for Healthcare Research and Quality (AHRQ) scale on five aspects: selection bias, performance bias, attrition bias, detection bias, and reporting bias ( 25 ). The quality of animal studies was evaluated by the CAMARADES checklist on seven aspects: sample size calculation, random allocation, blinded evaluation of outcomes, appropriate animal model, animal welfare, peer review, and conflict of interest declaration ( 26 ).…”
Section: Methodsmentioning
confidence: 99%